Characterization of the complete chloroplast genome of Malus baccata var. xiaojinensis. Issue 2 (3rd July 2019) - Ren, Yuan; Yan, Ming; Zhao, Xueqing; Chen, Xuesen; Yuan, Zhaohe
Abstract: Malus baccata var. xiaojinensis belonging to Rosaceae is not only an ornamental tree but also an apple genotype that is highly tolerant to Fe deficiency. In this study, we reported the complete chloroplast (cp) genome of M. baccata var. xiaojinensis using ILLUMINA sequencing. The whole cp genome is 160, 067 bp in length, containing a pair of inverted repeats (IRs) of 26, 358 bp, a large single copy (LSC) region of 88, 157 bp and a small single copy (SSC) region of 19, 194 bp. And, the overall GC content of the cp genome was 36.56%. A total of 110 unique genes were found in the cp genome. 17 genes were duplicated in the IRs, including six protein-coding genes, seven tRNA genes, and four rRNA genes. Fourteen genes contained one intron, whereas three genes ( rps12, clpP, and ycf3 ) contained two introns. The phylogenetic analysis demonstrated a close relationship between M. baccata var. xiaojinensis and Malus hupehensis .